WAJAH BARU PENDIDIKAN ISLAM INDONESIA: Jilbab, Toleransi, dan SKB 3 Menteri - Muh. Iqbal (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The problem of schools that apply rules for wearing school uniforms (hijab) as an imposition to use certain attributes and are considered intolerant and violate human rights. This is also the basis for the three ministerial decree on school uniforms issued as a form of government efforts to strengthen religious tolerance in educational institutions. This research uses literature study and data analysis in the form of content analysis. This study aims to analyze the background cases of the issuance of the SKB of three ministers from a recognized religious perspective in Indonesia and how the SKB strengthens religious tolerance in educational institutions. The results of the research are from the point of view of various religions, this case is the practice of religious teachings as part of dakwah (changing students for the better). SKB as a policy to strengthen tolerance between religions starting from educational institutions by not forcing students to use uniforms or attributes with specific religious characteristics..